Analysis of the Quality of Economic Growth in Districts/Cities in East Java - Utomo, Bayu Setyo; Sishadiyanti (Formosa Journal of Multidisciplinary Research, 2024)
The purpose of this study is to analyze the quality of economic growth of districts/cities in East Java using the Williamson index method and SWOT analysis.The Williamson Index is used to measure inequality and income distribution between counties/cities, and SWOT analysis is used to identify strengths, weaknesses, opportunities, and threats that impact regional economic growth.The study collects secondary data on regional gross domestic product (GRDP), per capita income, and other relevant variables from various public sources.The results show that there are significant differences in the quality of economic growth between districts/cities in East Java, with some regions showing strong and inclusive growth, while others show greater economic disparity. Shown.The SWOT analysis shows that internal factors such as infrastructure, human resources, and innovation, as well as external factors such as government policies and global economic conditions, play an important role in determining the quality of economic growth in the region.I am. Based on these findings, this study aims to improve the quality of economic growth in East Java, including increasing investment in education and infrastructure, strengthening interregional cooperation, and developing innovation and technology-based economic sectors. We recommend an integrated strategy.